2021
DOI: 10.1101/2021.09.20.461135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-target impacts of fungicide disturbance on phyllosphere yeasts in different crop species and management systems

Abstract: Fungicides reduce fungal pathogen populations and are essential to food security. Fungicide disturbance of plant microbiomes has received limited attention. Understanding the impacts of fungicides on crop microbiomes in different cropping systems is vital to minimizing unintended consequences while maintaining their use for plant protection. We used amplicon sequencing of fungi and prokaryotes in maize and soybean microbiomes before and after foliar fungicide application in leaves and roots from plots under lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
0
1
1
Order By: Relevance
“…Our study showed that the soybean fungal phyllosphere was dominated by Ascomycota with 97% of classified reads. However, Noel et al (2021) reported a high number of Basidiomycyete yeasts in the soybean phyllosphere, which was not identified as core microbiome in our study. This is possibly due to the choice of primers for sequencing and databases (eukaryote database or fungal database) for taxonomy assigiment.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Our study showed that the soybean fungal phyllosphere was dominated by Ascomycota with 97% of classified reads. However, Noel et al (2021) reported a high number of Basidiomycyete yeasts in the soybean phyllosphere, which was not identified as core microbiome in our study. This is possibly due to the choice of primers for sequencing and databases (eukaryote database or fungal database) for taxonomy assigiment.…”
Section: Discussioncontrasting
confidence: 77%
“…The microbiome composition differs between plant species, genotype (Sharaf et al 2019), and developmental stage (Copeland et al 2015). The communities can also be affected by different agricultural management, such as tillage, fertilization, and chemical treatment (Wattenburger et al 2019; Longley et al 2020; Karlsson et al 2014; Noel et al 2021). Understanding the effect of agricultural practices on the microbiome is important for the development of sustainable management strategies.…”
Section: Introductionmentioning
confidence: 99%